THE APPLICATION OF JIGSAW TASKS BY USING SCRAMBLED SENTENCES IN TEACHING READING DESCRIPTIVE TEXT - Brigitta Septarini Rahmasari; Andi Nurul Aini (UIBU, 2023)
This study aims to know the implementation of Jigsaw Tasks by using Scrambled Sentences in teaching reading descriptive text and its strengths and weaknesses. This is qualitative research. The data are collected using observation and interviews. Meanwhile, the data analysis uses three steps: reduction data, display data, and data verification. The results show that in the implementation of jigsaw tasks by using scrambled sentences, the students pay attention and listen to the explanation of the teacher during the teaching-learning process. They rearrange the jumble sentences card based on the pictures by adhering to the flannel board. The advantages are it could increase the student’s vocabulary mastery, and the jigsaw task technique with scramble sentences could motivate the students to understand the descriptive text and make the students focus on the material given. Besides, the students are active, enthusiastic, and enjoy learning to read descriptive text by using jigsaw tasks with scrambled sentences The disadvantages are the students make noise. Hence, his method is recommended for all teachers to use for teaching reading descriptive text and for future research to conduct the same research but in different fields.